Answer:
76
Step-by-step explanation:
So what you will need to do is subtract 2x - 3x = -x, then subtract three from both sides 8 - 3 and the answer will be -x + 5
1: -5 = 3m + c
2: -2 = 0 + c
From equation 2, we knew c = -2
So we sub into equation 1 and got the value of m
-5 = 3m - 2
m = -1
The equation of line is y = -x - 2
Answer:
Step-by-step explanation:
11x+6 = 15x-26
Answer:
x intercept is x=3
y intercept is y=-3
Step-by-step explanation:
We can write this equation in a simpler way to find the values needed. Lets do it. Take:
x-y=3
And sum y in both sides, as we know the equality will maintain:
x-y+y=3+y
x = 3+ y
Now subtract 3 in both sides:
x-3 = y+3-3
x-3=y
So, we can rewrite our equation as y=x-3
The x intercept is a value of x such that the equation in equal to zero; in other words, is the value of x when y is zero. It is also called a zero root. Graphically, its the x value when the function passes trough the x-axis. Lets find if, we nned that:
x-3 = 0
If we sum 3 in both sides:
x-3+3=3
x=3
So, x=3 is x intercept
For finding the y intercept we need the value of y when x is zero. Graphically, is the value of y obtained when the function passes trough the y-axis. So, replace x with 0:
0-3=y
y=-3
Another way to get it is knowing that the y intercept in a polynomial is always the independent term, the one that has no x or y, which in this case is -3.